The girl from the Savoy - Gaynor, Hazel (William Morrow, an imprint of HarperCollins Publishers, 2016)
At the Savoy hotel, two women with very different pasts try to forget the devastation of the Great War and forge a new life in a city where those who dare to dream can have it all. Dolly is the Savoy's newest chambermaid, whose proximity to the dazzling hotel guests fuels her dreams to be a star like her idol, Loretta May. Loretta, the daughter of an earl, has rebelliously turned her back on the ordered life expected of a society woman and lives as she likes, but holds a dark secret. When Dolly's life collides with Loretta's, they must both learn to let go of their pasts in order to hold on to what they most desire.--